Negative plate and preparation method thereof, lithium ion battery, battery pack and vehicle
By using a multi-layer coating structure combining small-particle graphite and large-particle graphite in the negative electrode sheet of the battery, the problem of improving the charging capacity of the negative electrode material in the fast charging direction is solved, and the high energy density and fast charging capacity of the battery are achieved.
Patent Information
- Application Number
- CN202411742159.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-05-02
AI Technical Summary
In the prior art, there are technical barriers to improving charging capacity in the research and development of the fast charging direction, which limits the development of fast charging core technology.
A negative electrode active layer with a combination of small-particle graphite and large-particle graphite is used to coat the negative electrode material active slurry on the current collector side to form a multi-layer coating structure to optimize the structure and performance of the electrode.
The energy density of the battery cell and the negative electrode charging capacity are improved, thereby significantly improving the fast charging capacity of the battery.
Smart Images

Figure BDA0005162811450000131 
Figure HDA0005162811460000011 
Figure HDA0005162811460000012
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a negative electrode sheet and a preparation method thereof, a lithium-ion battery, a battery pack and a vehicle. Background Art
[0002] In recent years, high-power charging technology has made significant breakthroughs, and 800V high-voltage fast charging piles have been rapidly expanded. Judging from the strategic layout of new energy vehicle models of domestic and foreign OEMs, ultra-fast charging models will be oriented towards large-scale application in the next one or two years, which has promoted the development of fast charging cell technology. However, the improvement of negative electrode charging capacity is currently the main factor restricting the development of fast charging cell technology. At present, there are still certain technical barriers to be overcome in the research and development of negative electrode materials in the direction of fast charging. Summary of the invention
[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose a negative electrode sheet to improve the negative electrode charging capacity, thereby improving the fast charging capacity of the battery.
[0004] In the first aspect of the present application, the present application proposes a fast-charging negative electrode sheet. According to an embodiment of the present application, the fast-charging negative electrode sheet comprises: a current collector and a negative electrode active layer disposed on at least one side of the current collector; wherein the negative electrode active layer comprises small-particle graphite and large-particle graphite, the median particle size of the small-particle graphite is 10μm-13μm, the median particle size of the large-particle graphite is 14μm-16μm, and the OI (I004 / I110) @ 1.6g / cc of the negative electrode sheet is 5 to 7. Small-particle graphite with a median particle size of 10μm-13μm has a higher specific surface area, which helps to increase the contact area with the electrolyte and increase the diffusion rate of lithium ions, thereby improving the charge and discharge rate of the battery; large-particle graphite with a median particle size of 14μm-16μm can provide better structural stability and lower internal stress, which helps to reduce the breakage of materials during the charge and discharge process; small-particle graphite and large-particle graphite in the negative electrode sheet with a moderate OI value have good crystallinity and order, which helps to improve the conductivity of electrons and the diffusion of lithium ions, thereby improving the charge and discharge performance of the battery. According to the negative electrode sheet of the embodiment of the present application, the energy density and negative electrode charging capacity of the battery cell can be improved, thereby improving the fast charging capacity of the battery.
[0005] According to an embodiment of the present application, the negative electrode active layer includes a first coating layer and a third coating layer stacked in sequence; wherein the first coating layer includes small-particle graphite, and the third coating layer includes large-particle graphite. According to the negative electrode sheet of the embodiment of the present application, the energy density and negative electrode charging capacity of the battery cell can be further improved, thereby further improving the fast charging capacity of the battery.
[0006] According to an embodiment of the present application, the negative electrode active layer further includes a second coating layer, and the second coating layer is disposed between the first coating layer and the third coating layer; the second coating layer includes large-particle graphite.
[0007] According to an embodiment of the present application, the porosity of the negative electrode active layer is 25%-45%.
[0008] According to an embodiment of the present application, the negative electrode active layer further includes a conductive agent and a binder.
[0009] According to an embodiment of the present application, the porosity of the first coating layer is 25% to 40%. The moderate porosity of the first coating layer helps to increase the diffusion rate of lithium ions in the electrode, because the pores provide channels for ion transmission, which can improve the charge and discharge rate of the battery; the moderate porosity of the first coating layer can maintain sufficient electron conduction paths; the moderate porosity of the first coating layer helps to accommodate the volume changes of the active material during the charge and discharge process, thereby reducing structural stress and cracking, and helping to improve the cycle stability and capacity retention rate of the battery. As a result, the moderate porosity of the first coating layer can increase the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capability of the battery.
[0010] According to an embodiment of the present application, the porosity of the third coating layer is 35%-45%.
[0011] According to an embodiment of the present application, the third coating layer further includes a low-silicon negative electrode material with a mass fraction of 3%-10%, and the size of the silicon grains is less than 2nm. Low-silicon negative electrode materials with a moderate mass fraction can reduce expansion and maintain a high energy density; the size of the silicon grains is less than 2nm, which can reduce stress concentration between silicon particles and reduce crack propagation caused by volume expansion. As a result, low-silicon negative electrode materials with a moderate mass fraction can increase the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capability of the battery.
[0012] According to an embodiment of the present application, the coating thickness ratio of the first coating layer, the second coating layer and the third coating layer is (3-5): (2-4): (2-4). The coating thickness ratio of each coating layer is moderate, which can optimize the structure of the electrode to achieve better electron and ion transmission, thereby improving the charge and discharge performance of the battery. Therefore, the moderate coating thickness ratio can improve the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capability of the battery.
[0013] According to an embodiment of the present application, the porosity of the second coating layer is 30%-40%.
[0014] In the second aspect of the present application, the present application proposes a method for preparing the negative electrode sheet described in the first aspect of the present application. According to an embodiment of the present application, the method includes coating an active slurry of negative electrode material on at least one side of the current collector to form a negative electrode active layer; wherein the active slurry of negative electrode material includes small-particle graphite and large-particle graphite, the median particle size of the small-particle graphite is 10μm-13μm, the median particle size of the large-particle graphite is 14μm-16μm, and the OI (I004 / I110) @ 1.6g / cc of the negative electrode sheet is 5 to 7. According to the method of the embodiment of the present application, a negative electrode sheet that improves the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capacity of the battery, can be prepared.
[0015] According to an embodiment of the present application, the method includes coating a first coating layer slurry on the current collector to form a first coating layer; and coating a third coating layer slurry on a side of the first coating layer away from the current collector to form a third coating layer. According to the method of an embodiment of the present application, the negative electrode multilayer coating can further prepare a negative electrode sheet that improves the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capacity of the battery.
[0016] According to an embodiment of the present application, the single-sided coating density of the first coating layer is 58-64 g / m 2 .
[0017] According to an embodiment of the present application, the single-sided coating density of the third coating layer is 43-46 g / m 2 .
[0018] According to an embodiment of the present application, the method further includes coating a second coating layer slurry on a side of the first coating layer away from the current collector to form a second coating layer; and coating a third coating layer slurry on a side of the second coating layer away from the first coating layer to form a third coating layer. According to the method of an embodiment of the present application, the negative electrode multilayer coating can further prepare a negative electrode sheet that improves the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capacity of the battery.
[0019] According to an embodiment of the present application, the coating thickness ratio of the first coating layer, the second coating layer and the third coating layer is (3-5): (2-4): (2-4). The coating thickness ratio of each coating layer is moderate, which can optimize the structure of the electrode to achieve better electron and ion transmission, thereby improving the charge and discharge performance of the battery. Therefore, the moderate coating thickness ratio can improve the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capability of the battery.
[0020] According to an embodiment of the present application, the single-sided coating density of the second coating layer is 43-46 g / m 2 .
[0021] In a third aspect of the present application, the present application proposes a lithium-ion battery. According to an embodiment of the present application, the lithium-ion battery comprises the negative electrode sheet described in the first aspect of the present application. According to the lithium-ion battery of the embodiment of the present application, the fast charging capability of the battery is significantly improved.
[0022] In a fourth aspect of the present application, the present application proposes a battery pack. According to an embodiment of the present application, the battery pack includes: a plurality of lithium-ion batteries described in the third aspect of the present application.
[0023] In a fifth aspect of the present application, the present application proposes a vehicle. According to an embodiment of the present application, the vehicle comprises: a plurality of battery packs as described in the fourth aspect of the present application.
[0024] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0026] Figure 1 This is a schematic diagram of the structure of a negative electrode sheet according to an embodiment of the present application.
[0027] Figure 2 This is a schematic diagram of the structure of a negative electrode sheet according to an embodiment of the present application.
[0028] Figure 3 This is a schematic diagram of the structure of a negative electrode sheet according to an embodiment of the present application.
[0029] Figure 4 This is a flow chart of a method for preparing a negative electrode sheet according to an embodiment of the present application.
[0030] Figure 5 This is a flow chart of a method for preparing a negative electrode sheet according to an embodiment of the present application.
[0031] Figure 6 This is a flow chart of a method for preparing a negative electrode sheet according to an embodiment of the present application.
[0032] Description of reference numerals:
[0033] 01: current collector; 02: negative electrode active layer; 03: first coating layer; 04: third coating layer; 05: second coating layer. DETAILED DESCRIPTION
[0034] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0035] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0036] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0037] In the description of the present application, it should be understood that the terms "width", "thickness", etc. indicate orientation or positional relationships based on the orientation or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0038] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.
[0039] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0040] In the description of the present application, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0041] In the description of the present application, “plurality” means two or more.
[0042] In the description of this application, "single-sided coating density" refers to the mass of this layer of active material coated on a single side of the current collector. According to the embodiments of this application, it specifically refers to the single-sided coating density of the phosphorus-based active layer on the current collector, the single-sided coating density of the thin graphene layer on the phosphorus-based active layer and the single-sided coating density of the hard carbon active layer on the thin graphene layer. This density will affect the volume energy density, charge capacity, overall performance of the battery and ultimately the cost of the battery.
[0043] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0044] In the description of this application, "OI (I004 / I110) @ 1.6 g / cc" refers to the ratio of the intensity of the diffraction peak I004 to the intensity of the diffraction peak I110 when the negative electrode sheet of the present application is compacted to 1.6 grams per cubic centimeter (g / cc). OI (Orientation Index) is a parameter used to measure the grain orientation of the material.
[0045] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0046] In the first aspect of the present application, the present application proposes a fast-charging negative electrode sheet. According to an embodiment of the present application, reference Figure 1The fast-charging negative electrode sheet 100 includes: a current collector 01 and a negative electrode active layer 02 disposed on at least one side of the current collector; wherein the negative electrode active layer includes small-particle graphite and large-particle graphite, the median particle size (D50) of the small-particle graphite is 10μm-13μm, for example, 10μm, 11μm, 12μm, 13μm and a range value of 11μm-13μm therebetween, the median particle size of the large-particle graphite is 14μm-16μm, for example, 14μm, 15μm, 16μm and any range value therebetween, the OI (I004 / I110) @ 1.6g / cc of the negative electrode sheet is 5 to 7, for example, 5, 6, 7 and any range value therebetween. The median particle size of small-particle graphite is moderate, and it has a high specific surface area, which helps to increase the contact area with the electrolyte, improve the diffusion rate of lithium ions, and thus improve the charge and discharge rate of the battery; the median particle size of large-particle graphite is moderate, which can provide better structural stability and lower internal stress, and help reduce the breakage of materials during the charge and discharge process; the small-particle graphite and large-particle graphite of the negative electrode sheet with a moderate OI value have good crystallinity and order, which helps to improve the conductivity of electrons and the diffusion of lithium ions, thereby improving the charge and discharge performance of the battery. According to the embodiments of the present application, the content of small-particle graphite and large-particle graphite in the negative electrode active layer is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or more. According to the embodiments of the present application, the optimized electrode structure helps to increase the insertion and extraction rate of lithium ions, thereby improving the energy density of the battery cell and the charging capacity of the negative electrode, and then improving the fast charging capacity of the battery.
[0047] According to the embodiments of the present application, reference Figure 2 , the negative electrode active layer 02 includes a first coating layer 03 and a third coating layer 04 which are stacked in sequence; wherein the first coating layer includes small-particle graphite, and the third coating layer includes large-particle graphite. According to an embodiment of the present application, the content of small-particle graphite in the first coating layer is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or more. According to an embodiment of the present application, the content of large-particle graphite in the third coating layer is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or more.
[0048] According to the embodiments of the present application, reference Figure 3, the negative electrode active layer 02 also includes a second coating layer 05, the second coating layer is arranged between the first coating layer and the third coating layer; the second coating layer includes large-particle graphite. According to the negative electrode sheet of the embodiment of the present application, the energy density and negative electrode charging capacity of the battery cell can be further improved, thereby further improving the fast charging capability of the battery. According to the embodiment of the present application, the content of large-particle graphite in the second coating layer is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or more.
[0049] According to an embodiment of the present application, the porosity of the negative electrode active layer is 25%-45%, such as 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45% and the range values 26%-45%, 27%-45% and 28%-45% therebetween. A moderate porosity of the negative electrode active layer helps to increase the diffusion rate of lithium ions in the electrode, because the pores provide channels for ion transmission, which can improve the charge and discharge rate of the battery; a moderate porosity of the negative electrode active layer can maintain a sufficient electron conduction path; a moderate porosity of the negative electrode active layer helps to accommodate the volume change of the active material during the charge and discharge process, thereby reducing structural stress and cracking, and helps to improve the cycle stability and capacity retention rate of the battery. Therefore, the moderate porosity of the negative electrode active layer can improve the energy density of the battery cell and the negative electrode charging capacity, thereby improving the fast charging capability of the battery.
[0050] According to an embodiment of the present application, the negative electrode active layer further includes a conductive agent and a binder.
[0051] According to an embodiment of the present application, the porosity of the first coating layer is 25% to 40%, such as 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39% and 40% and the range values 26% to 40%, 27% to 40% and 28% to 40% therebetween. The moderate porosity of the first coating layer helps to increase the diffusion rate of lithium ions in the electrode, because the pores provide channels for ion transmission, which can improve the charge and discharge rate of the battery; the moderate porosity of the first coating layer can maintain sufficient electronic conduction paths; the moderate porosity of the first coating layer helps to accommodate the volume change of the active material during the charge and discharge process, thereby reducing structural stress and cracking, and helping to improve the cycle stability and capacity retention rate of the battery. As a result, the moderate porosity of the first coating layer can improve the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capacity of the battery.
[0052] According to an embodiment of the present application, the porosity of the third coating layer is 35%-45%, such as 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45% and the range values 36% to 45%, 37% to 45% and 38% to 45% therebetween. The moderate porosity of the third coating layer helps to increase the diffusion rate of lithium ions in the electrode, because the pores provide channels for ion transmission, which can improve the charge and discharge rate of the battery; the moderate porosity of the third coating layer can maintain sufficient electronic conduction paths; the moderate porosity of the third coating layer helps to accommodate the volume change of the active material during the charge and discharge process, thereby reducing structural stress and cracking, and helping to improve the cycle stability and capacity retention rate of the battery. As a result, the moderate porosity of the third coating layer can improve the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capacity of the battery.
[0053] According to an embodiment of the present application, the third coating layer further includes a low-silicon negative electrode material with a mass fraction of 3%-10%, such as 3%, 4%, 5%, 6%, 7%, 8%, 9% and 10%, and the range values 3%-9% and 3%-8% therebetween; the size of the silicon grains is less than 2nm, such as 1nm, 1.1nm, 1.2nm, 1.3nm, 1.4nm, 1.5nm, 1.6nm, 1.7nm, 1.8nm and 1.9nm, and the range values 1nm-1.9nm, 1nm-1.8nm and 1nm-1.7nm therebetween. Low-silicon negative electrode materials with moderate mass fractions can reduce expansion and maintain a high energy density; the size of silicon grains is less than 2nm, which can reduce stress concentration between silicon particles and reduce crack propagation caused by volume expansion. As a result, low-silicon negative electrode materials with moderate mass fractions can increase the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capacity of the battery.
[0054] According to an embodiment of the present application, the silicon negative electrode of the third coating layer uses porous carbon as a substrate, CVD vapor deposition, and CVD carbon coating.
[0055] According to the embodiment of the present application, the process used for the silicon negative electrode of the third coating layer includes the following steps: using porous carbon as a matrix to provide a good structural basis for the silicon negative electrode material; depositing carbon materials, including amorphous carbon or graphene, on the porous carbon matrix by CVD technology to form a uniform carbon film with a certain thickness; the carbon coating layer can protect the silicon particles and reduce their direct contact and mechanical stress during the charge and discharge process, thereby improving the cycle stability and overall performance of the material. This CVD carbon coating technology helps to improve the electrochemical properties of silicon negative electrode materials, especially in improving their cycle stability and fast charging capabilities. Through this technology, lithium-ion battery negative electrode materials with higher energy density, better cycle performance and faster charging speed can be manufactured.
[0056] According to an embodiment of the present application, the first coating layer and the third coating layer further include a conductive agent and a binder.
[0057] According to an embodiment of the present application, the binder content of the first coating layer is 3.0%-3.4%, for example, it can be 3.0%, 3.05%, 3.1%, 3.15%, 3.2%, 3.25%, 3.3%, 3.35% and 3.4%.
[0058] According to an embodiment of the present application, the binder content of the third coating layer is 1.9%-2.3%, for example, it can be 1.9%, 1.95%, 2.0%, 2.05%, 2.1%, 2.15%, 2.2%, 2.25% and 2.3%.
[0059] According to an embodiment of the present application, the coating thickness ratio of the first coating layer, the second coating layer and the third coating layer is (3-5): (2-4): (2-4). The coating thickness ratio of each coating layer is moderate, which can optimize the structure of the electrode to achieve better electron and ion transmission, thereby improving the charge and discharge performance of the battery. Therefore, the moderate coating thickness ratio can improve the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capability of the battery.
[0060] According to an embodiment of the present application, the porosity of the second coating layer is 30-40%, for example, it can be 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39% and 40%, or a range of 31-40%, 32-40% therebetween.
[0061] According to an embodiment of the present application, the second coating layer further includes a conductive agent and a binder.
[0062] According to an embodiment of the present application, the binder content of the second coating layer is 2.5%-2.9%, for example, it may be 2.5%, 2.6%, 2.7%, 2.8% and 2.9%.
[0063] According to an embodiment of the present application, the conductive agent is selected from at least one of conductive carbon black, carbon fiber, Ketjen black, acetylene black, carbon nanotubes and graphene.
[0064] According to an embodiment of the present application, the binder includes at least one of polyvinylidene fluoride, styrene-butadiene latex, polyacrylic acid, polytetrafluoroethylene and polyethylene oxide.
[0065] In the second aspect of the present application, the present application proposes a method for preparing the negative electrode sheet described in the first aspect of the present application. According to an embodiment of the present application, the method includes coating an active slurry of negative electrode material on at least one side of the current collector to form a negative electrode active layer; wherein the active slurry of negative electrode material includes small-particle graphite and large-particle graphite, the median particle size of the small-particle graphite is 10μm-13μm, the median particle size of the large-particle graphite is 14μm-16μm, and the OI (I004 / I110) @ 1.6g / cc of the negative electrode sheet is 5 to 7. According to the method of the embodiment of the present application, a negative electrode sheet that improves the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capacity of the battery, can be prepared.
[0066] According to the embodiments of the present application, reference Figure 4 , the method comprising:
[0067] S100: coating a negative electrode material active slurry on one side of the current collector to form a negative electrode active layer.
[0068] According to an embodiment of the present application, the method includes coating a first coating layer slurry on the current collector to form a first coating layer; and coating a third coating layer slurry on a side of the first coating layer away from the current collector to form a third coating layer. According to the method of an embodiment of the present application, the negative electrode multilayer coating can further prepare a negative electrode sheet that improves the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capacity of the battery.
[0069] According to an embodiment of the present application, the single-sided coating density of the first coating layer is 58-64 g / m 2 , for example, it can be 58g / m 2 , 59g / m 2 , 60g / m 2 , 61g / m 2 , 62g / m 2 , 63g / m 2 and 64g / m 2 , or a range of 59-64g / m 2 , 60-64g / m 2 .
[0070] According to an embodiment of the present application, the single-sided coating density of the third coating layer is 43-46 g / m 2 , for example, it can be 43g / m 2 , 44g / m 2 , 45g / m 2 , 46g / m 2 Or the range between 44-46g / m 2 .
[0071] According to the embodiments of the present application, reference Figure 5 , the method comprising:
[0072] S1000: coating a first coating layer slurry on one side of the current collector to form a first coating layer;
[0073] S2000: coating a third coating layer slurry on a side of the first coating layer away from the current collector to form a third coating layer.
[0074] According to an embodiment of the present application, the method further includes coating a second coating layer slurry on a side of the first coating layer away from the current collector to form a second coating layer; and coating a third coating layer slurry on a side of the second coating layer away from the first coating layer to form a third coating layer. According to the method of an embodiment of the present application, the negative electrode multilayer coating can further prepare a negative electrode sheet that improves the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capacity of the battery.
[0075] According to the embodiments of the present application, reference Figure 6 , the method comprising:
[0076] S10000: coating a first coating layer slurry on one side of the current collector to form a first coating layer;
[0077] S20000: coating a second coating layer slurry on a side of the first coating layer away from the current collector to form a second coating layer;
[0078] S30000: coating a third coating layer slurry on a side of the second coating layer away from the first coating layer to form a third coating layer.
[0079] According to an embodiment of the present application, the coating thickness ratio of the first coating layer, the second coating layer and the third coating layer is (3-5): (2-4): (2-4). The coating thickness ratio of each coating layer is moderate, which can optimize the structure of the electrode to achieve better electron and ion transmission, thereby improving the charge and discharge performance of the battery. Therefore, the moderate coating thickness ratio can improve the energy density and negative electrode charging capacity of the battery cell, thereby improving the fast charging capability of the battery.
[0080] According to an embodiment of the present application, the single-sided coating density of the second coating layer is 43-46 g / m 2 .
[0081] In the third aspect of the present application, the present application proposes a lithium-ion battery. According to an embodiment of the present application, the lithium-ion battery includes: the negative electrode sheet described in the first aspect of the present application. According to an embodiment of the present application, the lithium-ion battery further includes a diaphragm and a positive electrode sheet; wherein the negative electrode sheet is arranged on at least one side of the diaphragm; and a positive electrode sheet, wherein the positive electrode sheet is arranged on a side of the diaphragm away from the negative electrode sheet. According to the lithium-ion battery of the embodiment of the present application, the fast charging capability of the battery is significantly improved.
[0082] In a fourth aspect of the present application, the present application proposes a battery pack. According to an embodiment of the present application, the battery pack includes: a plurality of batteries described in the third aspect of the present application.
[0083] In a fifth aspect of the present application, the present application provides a vehicle. According to an embodiment of the present application, the vehicle comprises: a plurality of batteries as described in the fourth aspect of the present application.
[0084] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.
[0085] Embodiment 1:
[0086] refer to Figure 6 , using a three-layer coating method and an extrusion coater for coating. After the preparation of the first, second and third slurries, a double-die double-gasket extrusion coater is used for three-layer coating. The coating thickness ratio of the first, second and third coating layers is (3-5): (2.5-3.5): (2.5-3.5) to obtain the final multi-layer coated negative electrode sheet; the above-mentioned negative electrode sheet is characterized by plane and cross-section SEM, showing that the electrode structure is a three-layer electrode with different pore sizes and porosities. The pore size and porosity of the first coating layer are small, and the pore size and porosity of the second and third coating layers are second. The active materials, conductive agents and binders of each coating layer are evenly distributed; the above-mentioned negative electrode sheet is assembled into a bare battery cell with the positive electrode sheet and the diaphragm; then, the three-electrode copper wire is processed and the three-electrode battery cell is produced, lithium-plated and tested. The specific technical process of the negative electrode multi-layer coating technology for the three-electrode negative electrode-reference potential enhancement method is as follows:
[0087] Step ①: The first coating layer slurry, i.e., the first slurry, is prepared by mixing the above-mentioned small-particle graphite (median particle size = 10.8 μm, OI (I004 / I110) @ 1.6 g / cc = 5), graphite: conductive agent (SP): carbon nanotube (CNT): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 95.5%: 1.0%: 0.3%: 1.3%: 1.9% in a blender to prepare the first slurry;
[0088] Step ②: preparing the second coating layer, i.e., the second slurry, by mixing the above-mentioned small-particle graphite (median particle size = 15 μm, OI (I004 / I110) @ 1.6 g / cc = 5), graphite: conductive agent (SP): carbon nanotube (CNT): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 95.9%: 1.0%: 0.3%: 1.1%: 1.7% in a blender to prepare the second slurry;
[0089] Step ③: The third coating layer slurry, i.e., the third slurry, is prepared by mixing the above-mentioned large-particle graphite (median particle size = 15 μm, OI (I004 / I110) @ 1.6 g / cc = 5) + low-silicon negative electrode (silicon grain size = 1.5 nm), graphite: SP: carbon nanotube (CNT): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR): polyacrylic acid (PAA) = 95.5%: 1.0%: 0.3%: 1.1%: 1.5%: 0.6% in a blender to prepare the third slurry;
[0090] Step ④: three-layer slurry coating, using a double-die double-gasket extrusion coater, coating the first slurry on the first coating layer, that is, coating on the side close to the current collector, coating the second slurry on the surface of the first coating layer, and coating the third slurry on the surface of the second coating layer. The coating thickness ratio of the first, second and third coating layers is 4:3.0:3.0, and the final multi-layer coated negative electrode sheet is obtained, and the OI (I004 / I110) @ 1.6 g / cc of the negative electrode sheet is 5;
[0091] Step ⑤: The above negative electrode sheet is characterized by plane and cross-section SEM, which shows that the electrode structure is a three-layer electrode with different pore sizes and porosities, the pore size and porosity of the first coating layer are smaller, and the pore sizes and porosities of the second and third coating layers are second, and the active material, conductive agent and binder of each coating layer are evenly distributed;
[0092] Step ⑥: Bare cell assembly, assembling the above-mentioned negative electrode sheet, positive electrode sheet and separator into a bare cell for use in the preparation of a three-electrode cell;
[0093] Step ⑦: treating the three-electrode copper wire and manufacturing the three-electrode battery cell. After treating the copper wire with a paint stripper, dilute sulfuric acid and anhydrous ethanol and vacuum drying, a diaphragm sleeve is manufactured, and the treated copper wire is buried in the bare battery cell. Then, the three-electrode battery cell is manufactured to obtain the three-electrode battery cell.
[0094] Step ⑧: Lithium plating of the three-electrode battery cell, using forward lithium plating: 30 microamperes for 10 hours, set aside for 12 hours; reverse lithium plating: 30 microamperes for 10 hours, set aside for 12 hours, to carry out lithium plating of the three-electrode battery cell;
[0095] Step ⑨: Three-electrode battery cell test, the charging strategy (MAP) test process is as follows (rated capacity cutoff), and the following test process and MAP table are used for three-electrode testing.
[0096] Set aside for 30 minutes;
[0097] 1C discharge to voltage of 2.75V;
[0098] Set aside for 1 hour;
[0099] The charging strategy uses constant current charging (the last step is constant voltage charging until the cut-off current is 0.05C);
[0100] Set aside for 1 hour;
[0101] 1C discharge to voltage of 2.75V;
[0102] Set aside for 1 hour.
[0103] The charging strategy (MAP) table is as follows:
[0104] SOC 0 5 10 20 25 35 40 50 55 60 65 70 75 80 90 97 100 magnification / 0.33 2 4.86 4.5 4.3 3.4 3.2 3.2 2.8 2.5 2.4 2 1.5 1.2 1 0.33
[0105] Example 2
[0106] It is basically the same as Example 1, except that the median particle size of the small-particle graphite particles of the first slurry in the first coating layer is 10.0 μm, the median particle size of the small-particle graphite particles of the second slurry in the second coating layer is 14 μm, and the median particle size of the large-particle graphite particles of the third slurry in the third coating layer is 14 μm, and the remaining steps are the same.
[0107] Example 3
[0108] It is basically the same as Example 1, except that the median particle size of the small-particle graphite particles of the first slurry in the first coating layer is 13 μm, the median particle size of the small-particle graphite particles of the second slurry in the second coating layer is 16 μm, and the median particle size of the large-particle graphite particles of the third slurry in the third coating layer is 16 μm, and the remaining steps are the same.
[0109] Example 4
[0110] It is basically the same as Example 1, except that the silicon grain size is 2 nm, and the other steps are the same.
[0111] Example 5
[0112] It is basically the same as Example 1, except that the OI (I004 / I110) @ 1.6 g / cc of the negative electrode is 7, that is, the OI (I004 / I110) @ 1.6 g / cc of the first coating layer, the second coating layer, and the third coating layer is 7, and the rest of the steps are the same.
[0113] Example 6
[0114] It is basically the same as Example 1, except that the coating thickness ratio of the first, second and third coating layers is 5:2.5:2.5, and the other steps are the same.
[0115] Example 7
[0116] It is basically the same as Example 1, except that the coating thickness ratio of the first, second and third coating layers is 3:3.5:3.5, and the other steps are the same.
[0117] Example 8
[0118] It is basically the same as Example 1, except that a double-layer coating method is adopted and an extrusion coater is used for coating. After the preparation of the first and third slurries, a double-layer coating is carried out using an extrusion coater with a double die head and double gasket. The coating thickness ratio of the first coating layer and the third coating layer is (3-5): (5-7) to obtain the final double-layer coated negative electrode sheet; the above-mentioned negative electrode sheet is characterized by plane and cross-section SEM, showing that the electrode structure is a double-layer electrode with different pore sizes and porosities. The pore size and porosity of the first coating layer are relatively small, and the pore size and porosity of the third coating layer are second. The active materials, conductive agents and binders of each coating layer are evenly distributed; the above-mentioned negative electrode sheet is assembled into a bare battery cell with a positive electrode sheet and a separator; then, the three-electrode copper wire is processed and the three-electrode battery cell is manufactured, lithium-plated and tested. The specific technical process of the negative electrode multi-layer coating technology for the three-electrode negative electrode-reference potential enhancement method is as follows:
[0119] Step ①: The first coating layer slurry, i.e., the first slurry, is prepared by mixing the above-mentioned small-particle graphite (median particle size = 10.8 μm, OI (I004 / I110) @ 1.6 g / cc = 5), graphite: SP: CNT: CMC: SBR = 95.5%: 1.0%: 0.3%: 1.3%: 1.9% in a blender to prepare the first slurry;
[0120] Step ②: The third coating layer slurry, i.e., the third slurry, is prepared by mixing the above-mentioned large-particle graphite (median particle size = 15 μm, OI (I004 / I110) @ 1.6 g / cc = 5) + low-silicon negative electrode (silicon grain size = 1.5 nm), graphite: SP: CNT: CMC: SBR: PAA = 95.5%: 1.0%: 0.3%: 1.1%: 1.5%: 0.6% in a blender to prepare the third slurry;
[0121] Step ③: Double-layer slurry coating, using a double-die double-gasket extrusion coater, coating the first slurry on the first coating layer, that is, coating on the side close to the current collector, and coating the third slurry on the surface of the first coating layer. The coating thickness ratio of the first and third coating layers is 4:6, and the final multi-layer coated negative electrode sheet is obtained, and the OI (I004 / I110) @ 1.6 g / cc of the negative electrode sheet is 5;
[0122] Step ④: The above-mentioned negative electrode sheet is characterized by planar and cross-sectional SEM, which shows that the electrode structure is a double-layer electrode with different pore sizes and porosities. The pore size and porosity of the first coating layer are smaller, and the pore size and porosity of the third coating layer are second. The active material, conductive agent and binder are evenly distributed in each coating layer, and the remaining steps are the same.
[0123] Example 9
[0124] It is basically the same as Example 1, except that a single-layer coating method is adopted, and an extrusion coater is used for coating. After the first slurry is prepared, an extrusion coater is used for single-layer coating to obtain a single-layer coated negative electrode sheet; the above-mentioned negative electrode sheet is characterized by plane and cross-section SEM, showing that the electrode structure is a single-layer electrode structure with a small pore size and porosity, and the active material, conductive agent and binder are evenly distributed; the above-mentioned negative electrode sheet is assembled into a bare battery cell with a positive electrode sheet and a diaphragm; then, three-electrode copper wire processing and three-electrode battery cell production, lithium plating and testing are carried out. The specific technical process of the three-electrode negative electrode-reference potential enhancement method with single-layer negative electrode coating is as follows:
[0125] Step ①: The first coating layer slurry, i.e., the first slurry, is prepared by mixing the above-mentioned small-particle graphite (median particle size = 10.8 μm, OI (I004 / I110) @ 1.6 g / cc = 5), graphite: SP: CNT: CMC: SBR = 95.5%: 1.0%: 0.3%: 1.3%: 1.9% in a blender to prepare the first slurry;
[0126] Step ②: single-layer slurry coating, using an extrusion coater to perform single-layer coating to obtain a final single-layer coated negative electrode sheet, the OI (I004 / I110) of the negative electrode sheet is 1.6 g / cc = 5;
[0127] Step ③: The above negative electrode sheet was characterized by plane and cross-section SEM, which showed that the electrode structure was a single-layer electrode structure with small pore size and porosity, and the active material, conductive agent and binder were evenly distributed. The remaining steps were the same.
[0128] Comparative Example 1
[0129] The process is basically the same as Example 1, except that the median particle size of the small-particle graphite is 9 μm, and the remaining steps are the same.
[0130] Comparative Example 2
[0131] It is basically the same as Example 1, except that the median particle size of the small-particle graphite is 14 μm, and the other steps are the same.
[0132] Comparative Example 3
[0133] The process is basically the same as Example 1, except that the median particle size of the large-particle graphite is 13 μm, and the remaining steps are the same.
[0134] Comparative Example 4
[0135] It is basically the same as Example 1, except that the median particle size of the large-particle graphite is 17 μm, and the other steps are the same.
[0136] Comparative Example 5
[0137] It is basically the same as Example 1, except that the OI (I004 / I110) @ 1.6 g / cc of the negative electrode sheet is 4, and the other steps are the same.
[0138] Comparative Example 6
[0139] It is basically the same as Example 1, except that the OI (I004 / I110) @ 1.6 g / cc of the negative electrode sheet is 8, and the other steps are the same.
[0140] Table 1: Comparison of negative electrode-reference safety potential data of three-electrode battery cells
[0141]
[0142] Comparing the test results of Example 1 with those of Comparative Examples 1 and 2, it can be seen that when the median particle size of small-particle graphite is reduced to 9 μm and the median particle size of small-particle graphite is increased to 14 μm, the negative electrode-reference safety potential of different SOCs is reduced. This indicates that when the median particle size of small-particle graphite is 10-13 μm, it is beneficial to improve the negative electrode-reference safety potential of different SOCs.
[0143] Comparing the test results of Example 1 with Comparative Examples 3 and 4, it can be seen that the median particle size of large-particle graphite is reduced to 13 μm, and the median particle size of large-particle graphite is increased to 17 μm, and the negative electrode-reference safety potential of different SOCs is reduced. This shows that when the median particle size of large-particle graphite is 14 μm-16 μm, it is beneficial to improve the negative electrode-reference safety potential of different SOCs.
[0144] Comparing the test results of Example 1 with Comparative Examples 5 and 6, it can be seen that when the OI (I004 / I110) @ 1.6 g / cc of the negative electrode sheet is 4 and 8, the negative electrode-reference safety potential at different SOCs is reduced. This indicates that when the OI (I004 / I110) @ 1.6 g / cc of the negative electrode sheet is 5 to 7, it is beneficial to improve the negative electrode-reference safety potential at different SOCs.
[0145] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0146] Although the embodiments of the present application have been shown and described above, it can be understood that the embodiments are illustrative and cannot be construed as limitations on the present application. A person skilled in the art can change, modify, replace and modify the embodiments within the scope of the present application.
Claims
1. A fast-charging negative electrode sheet, characterized in that: include: A current collector and a negative electrode active layer disposed on at least one side of the current collector; The negative electrode active layer includes small-particle graphite and large-particle graphite, the median particle size of the small-particle graphite is 10μm-13μm, the median particle size of the large-particle graphite is 14μm-16μm, and the OI (I004 / I110) @ 1.6g / cc of the negative electrode sheet is 5 to 7.
2. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active layer comprises a first coating layer and a third coating layer which are stacked in sequence; Wherein, the first coating layer comprises small-particle graphite, and the third coating layer comprises large-particle graphite.
3. The negative electrode sheet according to claim 2, characterized in that: The negative electrode active layer further includes a second coating layer, wherein the second coating layer is disposed between the first coating layer and the third coating layer; The second coating layer includes large particle size graphite.
4. The negative electrode sheet according to claim 1, characterized in that: The porosity of the negative electrode active layer is 25%-45%.
5. The negative electrode sheet according to claim 2, characterized in that: The porosity of the first coating layer is 25% to 40%; And / or, the porosity of the third coating layer is 35%-45%; And / or, the third coating layer further comprises 3%-10% by mass of low-silicon negative electrode material, and the size of silicon grains is less than 2nm.
6. The negative electrode sheet according to claim 3, characterized in that: The coating thickness ratio of the first coating layer, the second coating layer and the third coating layer is (3-5):(2-4):(2-4); And / or, the porosity of the second coating layer is 30%-40%.
7. A method for preparing the negative electrode sheet according to any one of claims 1 to 6, characterized in that: include: Coating a negative electrode material active slurry on at least one side of the current collector to form a negative electrode active layer; The negative electrode material active slurry includes small-particle graphite and large-particle graphite, the median particle size of the small-particle graphite is 10 μm-13 μm, the median particle size of the large-particle graphite is 14 μm-16 μm, and the OI (I004 / I110) @ 1.6 g / cc of the negative electrode sheet is 5 to 7.
8. The method according to claim 7, characterized in that The method comprises coating a first coating layer slurry on the current collector to form a first coating layer; A third coating layer slurry is coated on a side of the first coating layer away from the current collector to form a third coating layer.
9. The method according to claim 8, characterized in that The method further includes coating a second coating layer slurry on a side of the first coating layer away from the current collector to form a second coating layer; A third coating layer slurry is coated on a side of the second coating layer away from the first coating layer to form a third coating layer.
10. The method according to claim 8, characterized in that The single-sided coating density of the first coating layer is 58-64 g / m 2 ; And / or, the single-sided coating density of the third coating layer is 43-46 g / m 2 .
11. The method according to claim 9, characterized in that The coating thickness ratio of the first coating layer, the second coating layer and the third coating layer is (3-5):(2-4):(2-4); And / or, the single-sided coating density of the second coating layer is 43-46 g / m 2 .
12. A lithium ion battery, characterized in that: include: The negative electrode sheet according to any one of claims 1 to 6.
13. The lithium ion battery according to claim 12, characterized in that: Further comprising a separator and a positive electrode sheet; wherein the negative electrode sheet is disposed on at least one side of the separator; A positive electrode sheet is arranged on a side of the diaphragm away from the negative electrode sheet.
14. A battery pack, characterized in that: include: A plurality of lithium ion batteries according to claim 12 or 13.
15. A vehicle, characterized in that: include: The battery pack according to claim 14.